Konsep Dasar Manajemen Pendidikan sebagai Landasan Dalam Inovasi Pendidikan - Zohriah, Anis; Nafis Badri, Muhammad Shofwan Mawally (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Educational institutions are growing increasingly complex so that this requires a well-organized and correct organization. The basic concept of education management is needed as a basis for creating innovation in the field of education. This research uses a descriptive qualitative approach by examining existing literature. To become an innovative manager and able to create innovations in the world of education, it is very important to understand the basic concepts of education management. Keywords: management, education, educational management, educational innovation.